On the Issue of Pre-Contractual Liability Qualification - L. V. Shvarts; E. S. Deriabina (Теоретическая и прикладная юриспруденция)
The article is devoted to the study of the problem of the protectability of literary works and their components, expressed in the application of the doctrine of the protected form and unprotected content of a literary work as the main concept in domestic legislation and judicial practice. Within the framework of this article, the distinguished legally significant elements under Russian law, the criteria for their protection are analyzed. The author analyzes the influence of the teachings of I. G. Fichte on the protected form and unprotected content on the provisions of legislative acts regulating copyright protection, as well as cases of granting legal protection based on the criterion of the author’s creative work, for example, in relation to such elements of a literary work as the name and character.